A Review of Surgical Approach taken by Acharya Sushruta in the Management of Shataponaka Bhagandara w.s.r to Multiple Tract Fistula In Ano - Geeta; Kumar, Anil; Panja, Asit K; Gupta, Nisha (International Research Journal of Ayurveda & Yoga, 2023)
maharoga and discussed it in detail based on its prevalence and difficulty in treatment. Shatponaka Bhagandara is one of the five varieties of Bhagandara that Acharya Sushruta has mentioned. In an effort to reduce recurrence rates and increase success rate over the past many years, numerous authors have proposed innovative procedures. However, Fistula-in-Ano is still a challenging surgical condition. In order to manage this difficult condition and create new trends in our understanding of Fistula-in-Ano, it is necessary to rediscover the old wisdom of Acharya Sushruta. The objective of this study is to review and interpret the surgical approach taken by Acharya Sushruta in the management of Shatponaka Bhagandara in light of contemporary surgical literatures, which may hold the key for successful management of this disease.